Indirect diagnose of alcohol of abuse/dependency in an adult peruvian population: validation of a survey - Nizama-Valladolid, Martín (2010)
Objective: Validation of a survey for making an indirect diagnosis of abuse/dependence of alcohol survey in the Peruvian Andes. Material and method: We used the database of The Mental Health Epidemiological Study conducted in the Peruvian Andes in 2003, which includes surveys assessing mental health. We used the direct diagnosis of alcohol abuse/dependence module in adult males, and indirect diagnosis of alcohol abuse/dependence survey in their spouses. The sample size was 1,302 adult couples. Cronbachs Alpha coefficient was used in order to verify reliability of the tests. Validity of criteria was obtained by comparing them with the direct questionnaire and the validity of the construct was determined by using a factorial analysis. Results: The internal consistency of the questionnaire was 93.1%. The estimated probability of matching between the indirect survey and the external criteria is 77%. Best sensitivity (70.4%) and specificity (74.9%) values were located in 2 positive items. The factorial analysis indicated that most of the items saturate one predominant factor.   Conclusions: The questionnaire for indirect diagnosis of alcohol abuse/ dependence is partially valid in populations with similar characteristics to those from the Peruvian Andes.